Exploiting Lactoferricin (17–30) as a Potential Antimicrobial and Antibiofilm Candidate Against Multi-Drug-Resistant Enteroaggregative Escherichia coli - Vergis, Jess; Malik, Satyaveer Singh; Pathak, Richa; Kumar, Manesh; Ramanjaneya, Sunitha; Kurkure, Nitin Vasantrao; Barbuddhe, Sukhadeo Baliram; Rawool, Deepak Bhiwa (Frontiers in Microbiology, 2020)
The study evaluated in vitro antimicrobial and antibiofilm efficacy of an antimicrobial peptide (AMP), lactoferricin (17-30) (Lfcin [17-30]) against biofilm-forming multi-drug resistant strains of enteroaggregative Escherichia coli (MDR-EAEC) and further assessed its in vivo antimicrobial efficacy in a Galleria mellonella larval model. Initially, minimum inhibitory concentration (MIC; 32 µM), minimum bactericidal concentration (MBC; 32 µM), and minimum biofilm eradication concentration (MBEC; 32 µM) of Lfcin (17-30) were determined against MDR-EAEC field isolates (n=3). Lfcin (17-30) was tested stable against high-end temperatures (70oC and 90oC), the physiological concentration of cationic salts (150 mM NaCl and 2 mM MgCl2) and proteases (proteinase-K and lysozyme). Further, at lower MIC, Lfcin (17-30) proved to be safe for sheep RBCs, secondary cell lines (HEp-2 and RAW 264.7), and beneficial gut lactobacilli. In the in vitro time-kill assay, Lfcin (17-30) inhibited the MDR-EAEC strains 3 h post-incubation, and the antibacterial effect was due to membrane permeation of Lfcin (17-30) in the inner and outer membranes of MDR-EAEC. Furthermore, in the in vivo experiments, G. mellonella larvae treated with Lfcin (17-30) exhibited an increased survival rate, lower MDR-EAEC counts (P< 0.001), mild to moderate histopathological changes, enhanced immunomodulatory effect and were safe to larval cells when compared with infection control. Besides, Lfcin (17-30) proved to be an effective antibiofilm agent, as it inhibited and eradicated the preformed biofilm formed by MDR-EAEC strains in a significant (P< 0.05) manner both by microtitre plate assay and live/dead bacterial quantification- based confocal microscopy. We recommend further investigation of Lfcin (17-30) in an appropriate animal model before its application in target host against MDR-EAEC strains.